Immediate Modulation of Transcutaneous Auricular Vagus Nerve Stimulation in Patients With Treatment-Resistant Depression: A Resting-State Functional Magnetic Resonance Imaging Study - Sun, Jifei; Ma, Yue; Du, Zhongming; Wang, Zhi; Guo, Chunlei; Luo, Yi; Chen, Limei; Gao, Deqiang; Li, Xiaojiao; Xu, Ke; Hong, Yang; Xu, Fengquan; et al. (Frontiers in Psychiatry, 2022)
This is the first study using rs-fMRI to observe the mechanism of the immediate effect of taVNS treatment in patients with TRD.The results of this study showed that the cortico-striatal-pallidal-thalamic (CSPT) circuit was abnormal in the TRD group compared to the HC group. After 30 min of immediate treatment with taVNS in the TRD group, ALFF was reduced in the left orbital area of middle frontal gyrus and right middle frontal gyrus, but increased in the right superior orbitofrontal gyrus. In addition, the ROI-based FC between the left orbital area of middle frontal gyrus with left middle frontal gyrus and right inferior temporal gyrus was significantly increased.